The financing sustainability of long-term care insurance: an example from Nanning, China - Chen, Butong; Zhu, Xuhao; Wang, Huiyu; Zong, Lijie; Feng, Junqi; Tu, Sijing; Wang, Qianqiang (Frontiers in Public Health, 2025)
ObjectiveWith accelerated population aging in China, older adult services and long-term care for people with disabilities are becoming serious problems. Currently, mobilizing and allocating social resources, establishing reasonable financing mechanisms to address the growing demand for long-term care for those with disabilities, and ensuring the sustainable operation of long-term care insurance financing mechanism are vital.MethodsTaking Nanning, China, as an example, based on the Nanning Statistical Yearbook and relevant policy documents of government departments such as the medical care and security department, we use the PADIS-INT model and the International Labour Organization financing model(ILO Model) to estimate the contribution levels of Nanning’s residents’ long-term care insurance for the years of 2025, 2030, and 2035, and analyze the feasibility of the government’s and rural and urban residents’ individual contribution burden.ResultsThe average annual contribution amount of long-term care insurance for urban and rural residents will increase from 108.80 yuan in 2025 to 202.71 yuan in 2035. According to the sharing method, in which the government and individuals each bear 50% of the financing responsibility for long-term care insurance, the proportion of the government’s financial responsibility for the cost of long-term care insurance for urban and rural residents to the current year”s financial income will be 0.34, 0.42, and 0.50% in 2025, 2030, and 2035, respectively, and the amount of money that can be used by individual urban and rural residents to pay premiums from 2025 to 2035 will range from 10.7 to 16 thousand yuan.ConclusionThe finding shows that both the government and urban and rural residents can afford to pay future long-term care insurance costs; however, the long-term care insurance contributions of individual urban and rural residents in Nanning remain high. Hence, the Nanning municipal government should improve the awareness and participation rate of urban and rural residents in long-term care insurance; scientifically measure the financing level of long-term care insurance; establish a multichannel, scientifically reasonable, and dynamically adjusted long-term care insurance financing mechanism; and maintain the sustainable operation of the financing mechanism of long-term care insurance in Nanning.